ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN KONSUMEN MEMBELI IKAN CAKALANG (KATSUWONUS PELAMIS) SEGAR DI PASAR ARUMBAI KOTA AMBON - Nanlohy, Hellen; Saiful, Saiful; Angrainum, Ode Delvi (Universitas Pattimura, 2024)
The decision to purchase skipjack fish in Ambon City is influenced by a number of factors, namely price, quality, consumer income and sales location. The purpose of this study was to determine the characteristics of consumers buying fresh skipjack fish at Arumbai Market in Ambon City. The analysis used qualitative analysis, F test, T test and multiple linear regression. The method used is the descriptive method. Respondents as many as 67 people were taken by Purposive Sampling. Based on the results of the study, it is known that the characteristics of respondents who buy and consume skipjack fish in Arumbai Market in Ambon City are dominated by women, classified as productive age (36-45 years), high school education (SMA), have dependents below or equal to 3 people. Most respondents have jobs, as long as the most respondents come from Batu Merah Village, respondents have incomes below or equal to MSEs in Ambon City of Rp 2,731,502. The results of the T test analysis show that the factors that influence consumers' decisions to buy fresh skipjack fish at the Arumbai Market in Ambon City are the price variable (X1) with a significance value of 0.000, the quality variable (X2) with a significance value of 0.003, consumer income variable (X3) with a significance value of 0.001 and sales location variable (X4) with a significant value of 0.007.